Empowering Communities through Reading Literacy: a Community-based Action Research on Gordon College’s Reading Program Initiative in Olongapo City - Paguio, Darwin P.; Gadia, Ediric D.; Sardina, Dante P.; Geniza, Ginalyn N.; Amarille, Anna Theresa M. (PT FORMOSA CENDEKIA GLOBAL, 2025)
This community-based action research presents the implementation of the community-based reading program aimed at addressing the literacy needs of learners in Olongapo City. Utilizing the data from the stakeholders and barangay committees on education, the program identified learners requiring reading remediation and trained teacher education and communication students to deliver as implementers of the basic reading instructions. The action research initiative followed a structured framework: identifying needs, training implementers, program implementation, monitoring, and evaluation. The study emphasized the importance of evidence-based practices, community engagement, and reflective processes in developing sustainable educational interventions. It highlights the potential of targeted programs to foster academic growth and strengthen community partnerships in addressing the community's needs.